(3GdeMGSHI GdhWfjI (B:s (3fXGe GdMSGHGJ GdGbJUGOjI GdLRGFQjI(B(SCEA) /s - (3YdGe, YKeGfs; (3YRhR, CMeOs ((3GdLRGFQ (B: s (3CdaG ddhKGFb ddfTQ hGdJhRjY (B, s, 2023)
(3jVe GdSjGb GdJGQjNj dJWhQ GdeMGSHI GdhWfjI, GdGWGQ GdfXQj dfXGe GdeMGSHI GdhWfjI, fXGe GdMSGHGJ GdGbJUGOjI GdLRGFQjI, GdbWGYGJ GdGbJUGOjI hGdLOGhd GdeQcRjI, CeKdI hJWHjbGJ(B.s
(3HjHdjhZQGajG(B: (3U U(B213-217s
Keywords: (3GdeMGSHI GdMchejIs; (3GdfXGe GdeMGSHj GdehMOs; (3eQGLYI GdMSGHGJs